Fatores associados à fragilidade em idosos jovens e com idade acima de 75 anos que vivem na comunidade - Diniz, Maria Angélica Andreotti (2018)
Introduction: Frailty is defined as the physiological state of age-related physiological vulnerability resulting from reduced homeostatic reserve and decreased ability of the body to withstand stress. It is estimated that the prevalence of fragility is between 4% and 59% in men and women, respectively, aged 65 years or older living in the community. Early detection of frailty and care for the frail elderly can assist the health team in driving the effectiveness of actions with potential for health promotion and disease prevention. Objective: To analyze the factors associated with the physical frailty of young adults (60-74 years old) and over 75 years or older in a context of high social vulnerability. Method: This is a cross-sectional study carried out in the city of São Carlos with 303 elderly people living in a neighborhood of high social vulnerability. The following instruments were used: sociodemographic and health characterization, Fried fragility phenotype, Katz, Lawton scale, Mini Mental State Examination, Geriatric Depression Scale, Social Outcome Scale of the Medical Outcome Study, and the International Physical Activity Questionnaire. Descriptive statistics and logistic regression were used to analyze the data, considering p <0.05. The project was sent to the Research Ethics Committee of the Federal University of São Carlos, through the Brazil Platform, and was approved with the number of opinion 860.653/2014. Results: Of the 303 elderly interviewed, 12.2% were non-frail, 60.7% were pre-frail and 27.1% were frail. There was a prevalence of female (57.1%), age between 60-74 years (75.6%), 1 to 4 years of schooling (51.8%) and having a partner (57.4%). Factors associated with frailty in the elderly group were depressive symptoms (OR: 2.65 95% CI: 1.3-5.0) and in the longevity group, the factor associated with frailty was illiteracy (OR: 14.6 95% CI: 1.8-116.5). Older adults presented better means when compared to older people in the variables: schooling, cognitive alteration, number of medical consultations, physical activity level, number of falls, number of hospitalizations, number of medications and number of diseases. Conclusion: The results of this research may instigate professionals and health managers about the need to discuss and plan new strategies for health promotion and prevention of aggravating factors of fragility, respecting the differences found in the elderly at the beginning and at the end of old age.